Elaboración de un plan estratégico para el colegio fiscomisional nocturno Vicente Anda Aguirre de la ciudad de Loja. - Conza Azuero, Rosa Fernanda (2012)
The present project is focused especially in the elaboration of a Strategic Planning for the School Revenue Night misional Vicente Aguirre he/she walks, this way; as achieving an excellent attention and mainly to be able to offer to the community an efficient and opportune service. Because today in day the educational institutions center their attention in planning their strategic competitions and in satisfying from a better way to their users through an efficient and effective service that allows them to rationalize their resources, to be more productive and more competitive. As for the methods and techniques used in the present investigation, a direct observation was made to the School Vicente Aguirre he/she Walks, they were carried out some bibliographical consultations and the revision of documents what allowed to get the necessary information to be taken advantage of in the I diagnose situational of the school. To be able to determine a strategic analysis of the Institution, firstly it was opted to carry out the summary of data, so much internal as external of the institution, through the surveys carried out by means of a CENSUS to the students of the first one, second and third year of high school from all the specialties to their respective family parents; in the same way to the educational and administrative personnel, located inside the institution. In a special way he/she is carried out an interview to the Doctor Dalton Herrera all this in order to gathering pertinent and reliable information to determine if this Educational Area is pursuing with its made by which was created and if it is fulfilling the parameters of: Mission, Vision, Objectives, Political, following the indispensable methodology, you proceeded to carry out an analysis FODA directed to the institution, in order to settle down which the STRENGTHS are, WEAKNESSES, THREATS AND OPPORTUNITIES, with the purpose to strengthen or to attack, as it is the case, not without before to carry out a meticulous analysis of the result of the surveys whose deduction offered us the necessary tools to know that the establishment has an important acceptance. Inside the DISCUSSION of the present investigative work one carries out the proposal of strategic, and once detected Plan the problem, and established the causes and the effects, you ended up determining which the probable solution would be, what bears a womb of strategies that will be good to correct difficulties or inconveniences, to settle down as well as to strengthen opportunities and strengths. He/she fits to mention that to improve their operation inside the administrative part what rebounds to the administration of their directive directly therefore each outlined strategic objective he/she has their logical mark structured through PROBLEM, GOAL, STRATEGIES, POLITICAL, TACTICAL, TIME OF EXECUTION, THE RESPECTIVE COST, THEIR FINANCING AND THE RESPONSIBLE ones, each one of these objectives also contains their solution strategies. In the First Project the following thing is formulated: of taking advantage of to the maximum the technology, to be able to improve the service to the students, and here it is determined that it is as an important contribution for what the government offers, because the quality of the education becomes this way effective for the School. In the Second Project he/she intends in implementing tools or programs that facilitate the best evaluation for the educational one and be of benefit the shared knowledge this it will be reflected with the best knowledge in the educational one and service to the student and this way to have a bigger one welcomed and acceptance on the part of the population. In the Third Project he/she was carried out training programs for the whole personnel of the school and he/she was reflected this way the competitive level that you/they will have the students when their studies culminate. And lastly he/she is carried out a Fourth Project that it will be of designing a pertinent organizational structure to be able to administer in an excellent way the educational institution and to detail the duties and responsibilities that he/she has the current personnel of the institution so much elaborating a structural flowchart and a manual of functions which consists the position, hierarchical levels, lines of authority and their respective functions and characteristic of position. Finally you has ended up determining the CONCLUSIONS and RECOMMENDATIONS based on the study and carried out proposal and that they are started to consideration of this Educational Unit for their acceptance and setting that which is focused the diverse problems that the school possesses in its diverse aspects.